Fortunacjana z Akwilei "Komentarz do Ewangelii" - Kasprzak, Dariusz Antoni (Vox Patrum, 2024)
The discovery in 2012 of the complete text of the Commentary on the Gospels, by Fortunatianus of Aquileia, represents a major event in the history of 21st century patrology. Austrian patrologist and philologist Lukas Julius Dorfbauer discovered the anonymous commentary on Matthew's Gospel in the collections of the Cologne Cathedral Library in Codex 17 (K: Köln, Erzbischofl. Diozesan- und Dombibl. 17, p. IX1/4). Dorfbauer showed that the found commentary, except for the opening pages, dated to the early 4th century, is the Fortunatianus Aquileiensis Commentarii in evangelia, lost for more than 1600 years. In 2013 Dorfbauer announced his discovery, and began work on a critical edition of the text, which he published in CSEL 103 in 2017. Fortunatianus' commentary was likely written as an exegetical aid for the clergy of Aquileia in the early 4th century. In writing it, the Bishop of Aquileia relied on a lost commentary on the gospels written by Victorinus, Bishop of Poetovium, in the late 3rd century. The commentaries mentioned above are evidence of the successful reception of Origen's allegorical exegesis in the Western Church in the late 3rd and early 4th centuries.